The Effect Of Social Norms On Tax Payer Compliance Behavior - Yasyika Nuarita Putri (Profesional Muda Cendekia Publishing, 2021)
This study aims to analyze the influence of descriptive norm, injuctive norm,subjective norm and personal norm on tax compliance. This research wasconducted on individual taxpayer in the Kabupaten Sukoharjo. This researchused quantitative method. The sample used in this study were 100 respondentsindividual taxpayer. The data retrieval technique of this study uses simplerandom sampling. The data analysis technique used is multiple regression usingSPSS 22.0 program.The result showed that the descriptive norm and subjectivenorm had a significant positive effect on tax compliance. While the injungtivenorm and personal norm did not affect on tax compliance.